PENGEMBANGAN KOTARA (KOMIK CERITA RAKYAT) “ASAL MULA DESA ALIANTAN” UNTUK SISWA SEKOLAH DASAR - Silvia Eka Putri; Otang Kurniaman (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to develop folklore comic “Asal Mula Desa Aliantan” and to find out if qualifications folklore comic is worthy. The folklore comic was made by application Clip Studio Paint. The method in this study was a 4D model including define, design, develop, disseminate, and it was restricted to three steps. Data collecting used a questionnaire. The research instrument was validated by the experts. The type of data was quantitative which was analyzed by using assessment criteria guidelines for product quality. The validation from the expert found that using folklore comic “Asal Mula Desa Aliantan” for elementary school students was worthy. The average percentage from the design experts was 91.66% with the category of very feasible. The average percentage from the language experts was 92.70% with the category of very feasible. Then, the percentage from the users was 86.10% for the product design and 85.40% for the language use with the category of very feasible.